Leituras de um viajante público (1812-1846) : o homem da natureza brasileira, seus mundos e os outros - Andrade, Manoel Ribeiro (2017)
This text tries to understand the look of the public traveler Antonio Moniz de Souza on the natural environment and the Other from his travel literature, as result of the expeditions and observations made by the sertões of Brazil (interior of Sergipe, Alagoas, Bahia, Minas Novas and Rio de Janeiro), in the first half of the 19th century. His readings revealed an endogenous perception of Brazil that separated in two worlds: one of the workers and another of the unemployed, adopting a prism strongly marked by a rural and religious subjectivity. This naturalist, also called Brazilian Nature Man, wandered through the interior of the Colony and the Empire between 1812 and 1846, recording the potential of the Brazilian vegetable, animal and mineral kingdom. We present a narrative that uses the clues and social plots experienced by this subject and his contexts to better understand the representational constructions established between his private universe and his collective environment, in order to understand this encounter with the different. Therefore, it takes the publications of this inquirer of nature as a source, concentrating within the field of Cultural History, making use of the historiographic approaches of Microhistory and Biography and the domains of History of Representations and Environmental History.